Relativity and normativity as a challenge of subject- matter teaching and learning - Führer, Carolin; Tesch, Bernd; Balg, Dominik; Grewe, Bernd (Research in Subject-matter Teaching and Learning (RISTAL), 2022)
In a plural and democratic society teaching challenges not only arise from the conditionality and perspectivity of knowledge, convictions and value systems, but also from a postfactual thinking. Questions of how to deal with one’s own subject-specific norms are sometimes pushed into the background in academic subject didactics. The article shows the potential of interdisciplinary comparison by using the example of classroom communication norms within different disciplines with strong subject cultures. An exchange regarding relativity and normativity could profile the subject-specificity of knowledge and knowledge communication as a necessary orientation against simplification and disambiguation for teachers and students in an uncertain world.